PENGELOLAAN KEARSIPAN PADA SD ISLAM AL-AZHAR 34 MAKASSAR - Thahir, Muthahharah (Pascasarjana Universitas Negeri Makassar, 2014)
This study aims to determine the management of archives at Islamic Elementary School Of Al-Azhar 34 in Makassar which is includes the step of archival storage, maintenance, shrinkage, and destruction. The results showed that the management of archives at Islamic Elementary School Of Al-Azhar 34 in Makassar through: 1) The process of archival storage, which applied was only the standard storage system, that is standard through the alphabetical system and the date system; 2) The maintenance of archives, done by cleaning with vacuuming regularly, 3) The depreciation process of archive, which is an archive reduction efforts done by the removal, destruction or the means of delivery, and 4) The destruction process of archives, which is the process of conducting the physical destruction that ends archive function and have no use value and carried total and not able be known in both content and form.